2005
DOI: 10.1097/01.bcr.0000176881.94641.bd
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cell Levels Correlate with Proinflammatory Cytokine Increase in the Acute Phase of Thermal Injury

Abstract: Circulating endothelial cells (CECs) are increased in sickle cell disease, myocardial infarction, and acute lung injury. The purpose of this study was to determine whether CECs are a prognosticating marker for the development of pneumonia in burn patients with/without inhalation injury in addition to their relationship to proinflammatory cytokines. There were 24 patients: 6 with inhalation injury, 5 with burn only,and 13 with burn plus inhalation injury. CECs were measured by anchored cytometry (Clarient Chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In the context of burn injuries, Gill and colleagues12 showed by dual‐colour flow cytometry, using combinations of the markers CD133, CD144 (VE cadherin) and VEGF receptor 2, an acute but transient rise of EPCs24 in the circulation in eight patients following a more than 15 per cent TBSA burn. In 24 patients suffering thermal injury (mean 32 per cent TBSA burn), Kowal‐Vern and colleagues25 found that circulating endothelial cells, defined as larger CD146 + cells only26, were increased over those of healthy subjects at days 1 and 2 after the injury and continued to be significantly higher at day 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of burn injuries, Gill and colleagues12 showed by dual‐colour flow cytometry, using combinations of the markers CD133, CD144 (VE cadherin) and VEGF receptor 2, an acute but transient rise of EPCs24 in the circulation in eight patients following a more than 15 per cent TBSA burn. In 24 patients suffering thermal injury (mean 32 per cent TBSA burn), Kowal‐Vern and colleagues25 found that circulating endothelial cells, defined as larger CD146 + cells only26, were increased over those of healthy subjects at days 1 and 2 after the injury and continued to be significantly higher at day 7.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support a possible relationship between VEGF and CXCL12, acting as mobilizing agents after burn injury, and EPCs. However, vascular trauma and ischaemic injury promote the release of many other factors 25 , which could also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies involving human umbilical vein endothelial cells (HUVECs) suggest that apoptotic endothelial cells have the potential for binding and activating platelets by the increased expression of phosphatidylserine and loss of anticoagulant membrane components, thereby promoting a prothrombotic milieu [41,42]. While a causal relationship has not been established between CECs and inflammation, it is likely as raised number of CECs are seen in other inflammatory disease states such as vasculitis and acute thermal injury [43,44].…”
Section: Endothelial Dysfunction Inflammation and Thrombogenesismentioning
confidence: 99%
“…Furthermore, because all of the patients who required intubation in our study had scald burns greater than 15% TBSA and because burns greater than 15% TBSA have been shown to trigger a systemic inflammatory response, it is possible that activation of SIRS may play a role [5]. Burn injury is a trigger for activation of inflammatory mediators including proinflammatory cytokines [5,10]. Serum concentrations of interleukin-6 and tumor necrosis factor-α have been found to be elevated in the early stages of burn injury [9].…”
Section: Discussionmentioning
confidence: 98%